Studying breast cancer lung metastasis using a multi-compartment microfluidic device with a mimetic tumor-stroma interaction model - Bahareh Zarin; Laleh Rafiee; Sorosh Abdollahi; Maryam Vatani; Mohsen Hassani; Amir Sanati-Nezhad; Shaghayegh Haghjooy Javanmard (Translational Oncology)
Background: Understanding the mechanisms underlying the metastasis of breast cancer cells to the lungs is challenging, and appropriate simulation of the tumor microenvironment with mimetic cancer-stroma crosstalk is essential. β4 integrin is known to contribute to triggering a variety of different signaling cues involved in the malignant phenotype of cancer but its role in organ-specific metastasis needs further study. In this work, a multi-compartment microfluidic tumor model was developed to evaluate cancer cell invasion. Materials and methods: To model the primary tumor microenvironment, breast cancer cells (MCF7) and cancer-associated fibroblasts (CAFs) were co-cultured within the tumor compartment of the microfluidic chip while normal lung fibroblasts (NLFs) were seeded in a different compartment, as the secondary tumor site, separated from the tumor compartment via a Matrigel™ layer resembling the extracellular matrix. Results: The cytotoxic effect of β4 integrin blockade on cancer cells gradually increased after 48 and 72 h of co-culture. Invasion of breast cancer cells in both single and coculture models was characterized in response to β4 integrin blockade. The invasion rate and gap closure of MCF7/CAF_NLF was significantly higher than MCF7_NLF (P < 0.0001). β4 integrin inhibition reduced the rate of gap closure and invasion of both (P < 0.0001). Conclusions: Biomimetic microfluidic-based tumor models hold promise for studying cancer metastasis mechanisms. Precise manipulation, simulation, and analysis of the cancer microenvironment are made possible by microfluidics.